KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR TEMA INDAHNYA KEBERSAMAAN SUBTEMA 1 - Rahmawati, Dita; ., Suyitno; Prima A, Filia (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
The Effectiveness of Problem Based Learning Model on Learning on Learning Outcomes of The Theme of âIndahnya Kebersamaanâ in Sub-Theme 1 of Fourth Grade Students of SDN Pandean Lamper 03 Semarang. The purpose of this study was to determine the effectiveness of the use of Problem Based Learning model on Learning on Learning Outcomes of The Theme of âIndahnya Kebersamaanâ in Sub-Theme 1 of Fourth Grade Students of SDN Pandean Lamper 03 Semarang. The method of the research is quantitative research in Pre Experiment Design with One-Group Pretest-Posttest Design. The technique used is Nonprobability Sampling in the saturated sampling form. The results of research data analysis after getting treatment using the Problem Based Learning model obtained 39 students who completed with a percentage of 90.70% and 4 students who have not finished with a percentage of 9.30%. Calculation of the value of learning outcomes at the average value of posttest> pretest is 82.79> 54.77. This is evident in the final analysis using the t test known that the results of tcount> t table are 24.27> 1.53 at a significant tariff of 5%. The average value of students attitudes and skills also increases using the Problem Based Learning model. From the analysis, it can be concluded that the Problem Based Learning learning model is effective on the learning outcomes of the theme of Indahnya Kebersamaan in Sub-Theme 1 of Fourth Grade Students of SDN Pandean Lamper 03 Semarang. Keywords: Problem Based Learning Model, learning outcomes